Clinical management of Hypoplasic Amelogenesis Imperfecta: a challenge for multidisciplinary team. A case report - Maria Gabriela Acosta-de Camargo; Alfredo Enrique Natera-Guarapo; John Mangles (Universidad de Antioquia, 2021)
Amelogenesis imperfecta (AI) refers to a group of rare genetic disorders that involve tooth development and are passed down through families. Hypoplasic AI phenotypes include the absence of enamel as a result of a defect in the secretory stage. This case report describes the diagnosis and treatment of a patient with hypoplastic AI. The clinical implications include sensitive teeth, functional problems, and aesthetic complaining. The diagnosis was done through history, clinical examination and imaging. The intervention was performed by Direct Resin Veneers. This treatment showed to improve occlusion, esthetics, and selfimage of the teenager. The satisfactory clinical result has made it possible to avoid more invasive and expensive treatments.